Participatory Mechanism for Rice-Fish Culture in Waterlogged Lands in Canal Commands - Bhatnagar, P R; Sikka, A K; Singh, A K; Upadhyaya, A; Dhanphule, S S (Journal of Agricultural Engineering, 2006)
Waterlogging of low lands of canal command is a serious problem that turns fertile land unproductive. Rice-fish system was suggested to the farmers as one of the interventions for productive use of such lands. But due to difficulty in rice farming on account of high depth and prolonged water stagnation, farmers were reluctant to adopt the practice. An alternative involving construction of dug out fish refuge and raising the remaining portion of the field using the excavated soil was found appealing to farmers. Design of fish refuge for given water depth and field area available, was developed. The intervention was carried out in a participatory mode in the command of a distributary under Sone canal system with active participation and input sharing with a Self Help Group. A fish refuge covering 21% of 629 mÂ² of a field acquired on lease having 50-60 cm of water stagnation, was dug out and the excavated soil was used to raise rice field by 30 cm. This provided congenial conditions and rice yield of 5.6 t/ha (against the normal yield 3.75 t/ha in nearby fields) and fish yield of 2.5 to 3.2 t/ha was obtained in two years of the study, yielding a net profit of Rs 19,000 and 24,000 in the two years. It created overwhelming response from the farmers' community and about 52% of them, mostly from tail end of the command, were enthusiastic to adopt the intervention.